2016
DOI: 10.3892/etm.2016.3188
|View full text |Cite
|
Sign up to set email alerts
|

Effect of miR-19a and miR-21 on the JAK/STAT signaling pathway in the peripheral blood mononuclear cells of patients with systemic juvenile idiopathic arthritis

Abstract: Abstract.Overexpression of the components of the Janus kinase/signal transducer and activator of transcription (JAK/STAT) signaling pathway are key factors of the pathogenic mechanisms underlying systematic juvenile idiopathic arthritis (SJIA). The present study aimed to investigate the association between microRNA (miR)-19a, miR-21 and the JAK/STAT signaling pathway. A total of 20 patients with SJIA were included in the study, and peripheral blood mononuclear cells (PBMCs) from 20 normal controls were also co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…7A). A recent report demonstrated that miR-19a targets SOCS3 and modulates JAK-STAT signaling in juvenile idiopathic arthritis (14). We first determined SOCS3 expression from primary HSC exposed to HCV-exo.…”
Section: Resultsmentioning
confidence: 99%
“…7A). A recent report demonstrated that miR-19a targets SOCS3 and modulates JAK-STAT signaling in juvenile idiopathic arthritis (14). We first determined SOCS3 expression from primary HSC exposed to HCV-exo.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study [17], thirty-three active phase JIA patients, aged from 2 to 14 years, who were seen in the Rheumatology Department of Guangzhou Women and Children's Medical Center, May 2017-July 2018, were included in this study. They belonged to two subgroups of JIA: systemic juvenile idiopathic arthritis (sJIA) (data were reported in a previous publication) [17] and polyarticular juvenile idiopathic arthritis (pJIA), conforming to the JIA classification of the 2001 International League of Associations for Rheumatology [18]. Twenty normal control patients were recruited from the Health Care Section of the hospital (the control data were reported in the previous publication) [17].…”
Section: Baseline Collectionmentioning
confidence: 99%
“…In our previous study [17], we have explored the relationship between miR-21 and JAK/STAT signal pathway in rheumatoid peripheral blood mononuclear cells (PBMCs). However, it still has not been identified if miR-21 can exert its function by combining STAT3 directly.…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic factors including microRNA are potent modifiers of gene expression programs, and as such there is burgeoning interest in defining their roles in inflammation and rheumatic diseases. Indeed, several reports have highlighted altered circulating or cellular microRNA levels in SJIA . Our previous monocyte microRNA expression profiling identified a broad spectrum of microRNA with altered expression in children with active SJIA .…”
Section: Discussionmentioning
confidence: 74%